On Modernity, Democracy, and Secularism: Reflections on the Malaysian Experience - Joned, Alima (Journal of Malaysian and Comparative Law, 2008)
As a myriad of challenges confront today’s Muslims, some modernists believe the solution lies in democracy. However, they are divided on the strategy of making democracy take root in Muslim countries. Inspired by Turkey, a number of modernists call for the secularisation of the political system. Specifically, they propose that Islam is confined to a private creed, without legal, political, or economic influence in the government. Some even take a position that secularism is the sine qua non of democracy and modernity. This article is a reaction to this proposition by reflecting on Malaysia’s experience with democracy and modernisation. As background, the article discusses briefly the ongoing debate on the compatibility of Islam and democracy. It then looks at Art 4 of the Malaysian Constitution to assess the extent to which Malaysia can be called a secular state before concluding that the Malaysian system is a mixed one where, as a matter of constitutional law, Malaysia is a parliamentary democracy with strong secular and Islamic institutions. In discussion that follows, the article offers analysis of several of the reasons why secular and Islamic traditions have enjoyed a peaceful co-existence. The article also evaluates measures put in place by the Malaysian Government to counter the growing appeal of political Islam during the 1980s that threatened the delicate balance between the secular and the religious. The article concludes by outlining some of the new challenges confronting Malaysia that must be addressed before the Malaysian system can mature as a viable alternative to the unbridled secularism of Turkey.